PENGARUH PEMBERIAN TERAPI MUSIK TERHADAP KECEMASAN PASIEN PRE GENERAL ANESTESI DI RS PKU MUHAMMADIYAH YOGYAKARTA - Ichtiarfi Waryanuarita; Induniasih Induniasih; Yustiana Olfah (Poltekkes Kemenkes Yogyakarta, 2018)
Pre operative anxiety occur in patients that undergoing anesthesia procedure and elective surgery. Music therapy is one of distraction technique , because music can reduce physiological pain, stress, and anxiety. Music therapy pushed down sympathy nerve system that reduce body stress respons. Music cause the brain release endorphine, increase dopamine level, and help rise up safety feeling. Find out the effect of music therapy to anxiety in pre general anesthesia patients in PKU Muhammadiyah Yogyakarta Hospital. This study uses a quasy experimental which aims to see the difference in pre anesthesia anxiety before and after given music therapy in intervention and control group. This study uses quasy experimental design here takes group pre test and post test with control sort design. Patients is given pre test and post test with APAIS scale, in intervention group with treatment. Samples in this study amounted to 20 respondents of control group and 20 respondents of intervension group. Data collection is done on May to June 2017. The result of collected data were processed using Wilcoxon test with significant ? = 0,05. There is a difference of anxiety before and after in the intervention group using music therapy. Wilcoxon test results obtained Sig. 0,000 (<0.05) so that H1 is accepted or rejected H0. There is a significant effect of music therapy to anxiety on pre general anesthesia patients in PKU Muhammadiyah Yogyakarta Hospital.